2017
DOI: 10.1063/1.4977568
|View full text |Cite
|
Sign up to set email alerts
|

Methane dissociation process in inductively coupled Ar/H2/CH4 plasma for graphene nano-flakes production

Abstract: The role of hydrogen and methane dissociation process in induction plasma synthesis of graphene nano-flakes (GNF) is studied by the optical emission spectroscopy of Ar/H2/CH4 plasma. The condensation of C2 species formed due to methane decomposition produces GNF, which depends on pressure. Electron impact and dehydrogenation processes dissociate methane, which promotes and hinders the GNF production, respectively. The effect of hydrogen is insignificant on quality, size and morphology of the GNF. The CH4 flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In some cases, even pure carbon products can be considered valuable in some forms, e.g. graphene nano-akes 83 and sheets. 84 For a much more in-depth review of this particular process, the reader is referred to an extensive recent review by Scapinello et al 85 The product selectivity of the process depends greatly on the gas temperature of the plasma, many times referred to as the "plasma warmness".…”
Section: Non-oxidative Ch 4 Conversionmentioning
confidence: 99%
“…In some cases, even pure carbon products can be considered valuable in some forms, e.g. graphene nano-akes 83 and sheets. 84 For a much more in-depth review of this particular process, the reader is referred to an extensive recent review by Scapinello et al 85 The product selectivity of the process depends greatly on the gas temperature of the plasma, many times referred to as the "plasma warmness".…”
Section: Non-oxidative Ch 4 Conversionmentioning
confidence: 99%
“…Nanomaterials 2020, 10 13 of 18 Recent research suggests that the C2 radicals are the main precursor species of graphene flakes [21,25,28]. In the Ar-H2 atmosphere, the formed C2 radicals can be consumed due to the formation of hydrocarbons by collision with the hydrogen molecules through the reaction [73,74]: C2 + H2 → C2H + H, so the synthesis rate of graphene flakes decreases.…”
Section: Synthesis Rate/yieldmentioning
confidence: 99%
“…Their research revealed that factors influencing graphene flakes synthesis include the precursor type, reactor design, flow rate of buffer gas, etc. Pristavita et al [23][24][25][26][27][28] and Cheng et al [29] developed a radio-frequency plasma system for graphene flakes synthesis via methane decomposition. Their study indicated that a high reaction temperature and addition of H 2 may promote the transformation of products from spherical particles to graphene flakes.…”
Section: Introductionmentioning
confidence: 99%
“…With the emergence and development of advanced processing techniques, CH 4 has received extensive attentions and applications in such fields as nanomaterial synthesis, crop fertilization, and syngas (H 2 +CO) production. [1][2][3] Meanwhile, carbon dioxide (CO 2 ) lies in atmosphere, marsh gas, and oilfield associated gas, playing the significant role in both natural ecological balance and modern society operation by ways of photosynthesis, fuel combustion, and organic decomposition. 4,5 It is well known that CH 4 and CO 2 are undesirable greenhouse gases, so the simultaneous utilization of CH 4 and CO 2 is essential to ensure the energy security of fossil fuels and reduce the greenhouse effect caused by climate changes.…”
Section: Introductionmentioning
confidence: 99%